Tumor Microenvironment Responsive and Platelet Membrane Coated Polydopamine Nanoparticles for Cancer Radiosensitization by Inducing Cuproptosis - Xin L; Ning S; Wang H; Shi R (International Journal of Nanomedicine)
Le Xin,1 Shipeng Ning,2 Hongwei Wang,1,3 Runze Shi4 1Department of General Surgery, Longgang Central Hospital of Shenzhen, Shenzhen, 518116, People’s Republic of China; 2Department of Breast Surgery, The Second Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi, 530031, People’s Republic of China; 3Department of General Surgery, Guangdong Provincial Key Laboratory of Precision Medicine for Gastrointestinal Tumor, Nanfang Hospital, Southern Medical University, Guangzhou, Guangdong, 510515, People’s Republic of China; 4The Second Ward of Breast Surgery, Cancer Hospital Affiliated to Harbin Medical University, Harbin, 150086, People’s Republic of ChinaCorrespondence: Hongwei Wang; Runze Shi, Email 360873476@qq.com; shirz@hrbmu.edu.cnBackground: Cuproptosis, distinguished from apoptosis, necroptosis, pyroptosis, and ferroptosis, is a current form of programmed cell death that provides novel strategies for tumor therapy. Nanotechnology inducing cuproptosis showed potential in tumor ablation. However, these strategies might induce cellular damage due to a lack of tumor-targeting ability or insufficient tumor inhibition alone.Methods: Here, biomimetic copper-doped polydopamine nanoparticles (PC NPs) were developed to specifically induce tumor cell cuproptosis to enhance radiotherapy (RT). PC NPs were characterized before application for tumor ablation.Results: These PC NPs improve tumor targeting and accumulation. After entering the tumor region, PC degrades in cells responsive to acidic tumor microenvironment (TME). Next, Cu2+ is reduced to Cu+ after consuming overexpressed glutathione (GSH), which induces dihydrolipoamide S-acetyltransferase (DLAT) aggression and cuproptosis. Under RT, reactive oxygen species (ROS) are generated and consume GSH, leading to cuproptosis. The decreasing of GSH content in tumor tissues can improve the treatment effect of RT by inhibiting self-repair of tumor cells, hindering cell survival and proliferation. The combination of PC and RT alleviate tumor growth, reaching a tumor growth inhibition rate of 93.0%.Conclusion: This tumor-specific targeting nano platform is a valuable radiosensitizer responsive to TME for improving therapeutic efficacy against tumors.Keywords: platelet cell membrane, radiosensitization, tumor microenvironment, cuproptosis, tumor therapy